Penanganan imigran dan terorisme di Uni Eropa - Ina Rohana Hutasoit; Adya Rosyada Yonas; Henny Saptatia Drajati Nugrahani (JPPI (Jurnal Penelitian Pendidikan Indonesia), 2021)
This study focuses on immigrants and terrorism, one of the main priorities of the European Union (EU), aims to explain how European Union's efforts in dealing with it. This study uses a qualitative approach with descriptive analysis method, structured to determine the legal rules established by the EU in dealing with developing of terrorism and immigrants. EU develops strategies and directives to deal with it in its Member States. EU seems unable to accommodate the wishes of the European community. Significantly, social movements initiated by the community were driven by actions based on hatred against refugees such as demonstrations, hate speech, to discrimination against refugees. Then Common European Asylum System (CEAS) was formed to make Europe a place that is open to refugees while still paying attention to the community's response then policies taken by EU can continue to protect interests of  European community.